A new replacing name for Andropogon decipiens (Campbell) E. Bridges & Orzell (Poaceae: Andropogoneae) - Deshmukh, Umakant Bhoopati; Shende, Mukund Bapurao; Reddy, Eanguwar Srinivas (Phytotaxa, 2022)
N/A